HLA frequency and prognosis in lung cancer. - Ford, C. H. (Nature Publishing Group, 1981)
In 100 patients with lung cancer we have found no significant abnormality in overall HLA antigen frequency when compared to a control sample of 151 random health individuals from the same region, though there was a high relative risk of being HLA-BW22-positive and having lung cancer. There was an increased frequency of HLA-B5 in small-(oat-)cell anaplastic carcinomas (P less than 0.05); HLA-B15 in anaplastic tumours (P less than 0.05); HLA-B40 in Stage III patients (P = 0.05) and a decreased frequency of HLA-B12 in adenocarcinomas (P less than 0.05). In 86 patients followed up for 2 1/2-5 3/4 years after surgery we have been unable to confirm the significant association of HLA-AW19 and/or HLA-B5 with good prognosis as reported by others. The most striking observation was that the frequency of HLA-BW22 was significantly higher in patients alive at least 2 1/2 years after surgery when compared to the control groups (P less than 0.05) and 83% of patients HLA-BW22-positive are alive compared to only 52.5% of lung cancer patients lacking this antigen. However, all the P values become nonsignificant when multiplied by the number of antigens studied, and these observations need further investigation in a large, prospective study.